Difficulties for a decolonial academic-scientific-school opening and possibilities from a community-indigenous-autonomous education: Difficulties for a decolonial academic-scientific-school opening and possibilities from a community-indigenous-autonomous education - JIMÉNEZ-NARANJO, Yolanda (Utopía y Praxis Latinoamericana, 2022)
In this document we include a questioning of academic-scientific-school knowledge that denies indigenous-community knowledge, actions and ways of life that limit the development of an indigenous-community and autonomous education (intercultural, decolonial or critical according to other statements). We initially address the plural (in) capacity of scientific-academic-school knowledge to link with other educational practices that are fundamentally communal, in many non-capitalist senses, where life (and knowledge) are fundamentally in relation to others, and where the human-animal-nature are embraced. This meeting reveals a scientific-academic-school knowledge that is individualistic, logocentric, meritocratic-individual, artificial and cumulative-extractivist. And it is mainly in the world that inhabits it, that is, in its onto-epistemic dimension. We conclude, with the contributions that some community educational experiences are making to this debate, who are precisely eroding the logics of knowledge and learning mentioned above by other more collective, cooperatives, situated to their own needs and knowledge.